SrTiO3-SiO2 oxide films for possible high-k gate dielectric applications - Lin, Chun-Chieh; Lai, Li-Wen; Lin, Chih-Yang; Tseng, Tseung-Yuen (My University, 2007)
Amorphous thin films of SrTiO3-SiO2 high-k dielectric oxides were deposited on p-Si substrate by sputtering from the targets made by SrTiO3 and SiO2 powder mixtures. The surface morphology, crystal structure, chemical bonding configuration, and depth profile of the composition were investigated by using scanning electron microscopy, glancing incident angle X-ray diffraction, X-ray photoelectron spectroscopy, and Auger electron spectroscopy, respectively. The capacitance-voltage (CV) and current-voltage characteristics were used for demonstrating their electrical properties. The SrTiO3-SiO2 thin films remained as amorphous structures when annealed up to 900 degrees C. The Pt/SrTiO3-SiO2/Si MOS structure 2 had a low leakage current density of similar to 2 x 10(-8) A/cm(2) measured at 100 kV/cm and dielectric constant of 24 for 700 degrees C-annealed film. The films annealed at 600 degrees C showed typical CV characteristics. However, the deformed CV curves were found for films annealed at 700 degrees C due to the diffusion of Ti species in the SrTiO3-SiO2 film into the Si substrate. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: high-k; gate oxide; leakage current; dielectric constant